(3MGTjI Ydi GdeWhd TQM JdNjU GdeaJGM ddJaJGRGfjs - (3GdSeQbfOj, efdG RGOg, CMeO Hf YKeGf, J(B901(3g`s ((3YHO Gddg Hf HTjQ GdHhSfhjs)
(3ChdgG (B:s
(3bGd GdTGQM QMeg Gddg(B: (3GdMeO ddg hgh bO PcQ acajfG eDfJg GdPj CdgefG GdEdgGe EjbGY GdTjA aj GdNjQ aj GdbdH HWQjb GdajVs
(3BNQgG (B:s
(3Ydjc PGc Cj TO heWQ Yf Cj TOjO hbdjd GdeQGe jbGd Yf GdTjA EPG bd dG jcGO jhLO hGddOO TOI GdNUheI hGdLOGd GdNUheI , hGdLRjd GdYXjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 192s
(3cTa GdXfhf(B: 2 / 476s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs